Colonic Endoscopic Tubing Is Safe and Effective Approach for Washed Microbiota Transplantation in Autistic Children - Qing-Fen Yuan; Hui-Yi Wu; Xian-Yun Chen; Ya-Mei Zheng; Song-Lin Fu; Xing-He Wang; Jian-Wei Zhu; Jian-Dong Guo; Xing-Xiang He; Li-Hao Wu (Gastroenterology Research and Practice)
Background. Washed microbiota transplantation (WMT) as the improved methods of fecal microbiota transplantation has been employed as a therapeutic approach for ameliorating symptoms associated with autism spectrum disorder (ASD). In this context, colonic transendoscopic enteral tubing (TET) has been utilized as a novel procedure for administering WMT. Methods. Data of children with ASD who received WMT by TET were retrospectively reviewed, including bowel preparation methods, TET operation time, success rate, tube retention time, the comfort of children, adverse events, and parent satisfaction. Results. A total of 38 participants underwent 124 colonic TET catheterization procedures. The average time of TET operation was 15 minutes, and the success rate was 100% (124/124). There was no significant difference in TET operation time between high-seniority physicians and low-seniority physicians. In 123 procedures (99%), the TET tube allowed the completion of WMT treatment for 6 consecutive days. In 118 procedures (95.2%), the tube was detached spontaneously after the end of the treatment course, and the average TET tube retention time was 8 days. There was no incidence of tube blockage during the treatment course. No severe adverse events occurred during follow-up. Parents of all participants reported a high level of satisfaction with TET. Conclusion. Colonic TET is a safe and feasible method for WMT in children with ASD.